Ovarian cyst in a newborn: a case report - V.A. Caiulo; S. Caiulo; C. Gargasole; G. Latini (PAGEPress Publications, 2012)
The presence of ovarian cysts in the newborn is often a sign of an abnormal exacerbation of the physiologic process. In our case a large cyst caused symptoms related to gastroesophageal reflux: vomiting, poor weight gain, and respiratory disorders. Ultrasound examination enabled a correct diagnosis.